Researches on Veterinary Medicine in Turkey: I. Veterinary Education - Ozen, Abdullah; Dogan, Ozlem; Gul, Raziye Tamay Basagac; Ozkul, Turel; Yuksel, Erhan (Kafkas Univ, Veteriner Fakultesi Dergisi, 2012)
Although there are limited number studies on general condition of veterinary education and its problems and solution offers of these problems in Turkey, any comprehensive studies in Turkey were not made. This study was carried out with the aim of determining veterinary education efficiency of veterinarians and veterinary faculty students and possible problems in education and the solutions of these problems. For this aim two questionnaires were developed for collecting data and one was applied to veterinary students and the other was applied to veterinary practitioners. The questionnaires applied by interviewing with 1176 participants individually in cities of seven geographical regions of Turkey that have a veterinary faculty. The data were analyzed: the efficiency of the education of veterinary faculties was evaluated as low: While the sufficiency of structure and duration were accepted as the strong sides of education, the insufficiency of practical training was considered as the weakness. In conclusion, in accordance with the opinions of participants it can be said that the problems in veterinary education in Turkey can be solved by increasing practices and decreasing faculty number and student quota.
Türkiye'de veteriner hekimli?i üzerine araştırmalar: I. veteriner hekimli?i e?itim-ö?retime
Keywords: Turkey; Undergraduate education; Veterinary medicine; Veterinary education